Candidal sepsis thoracic patient - V. I. Desyaterik; S. P. Mikhno; V. M. Miroshnitcenko; S. P. Voycak; S. K. Masalsky (Сучасні медичні технології)
Candidiasis infection is an actual problem in medical practice, which is due to the complexity of its diagnosis and severe complications during dissemination. The article presents a clinical case of candidal sepsis in a patient with a thoracic profile.